Mechanical behaviour of the in vivo paediatric and adult trunk during respiratory physiotherapy. (January 2014) - Zhu, Yumin; Bruyère-Garnier, Karine; Mitton, David; Vajda, Emmanuel; Bermond, François
The load–deflection response of the human trunk has been studied using various methods. The different shapes observed may be due to the methodology and the population. The purpose of this study is to quantify and explain the in vivo mechanical response of paediatric and adult trunks during respiratory physiotherapy. Eight children aged 5–15 months and eight healthy adult volunteers aged 30–87 years participated in this study. The force applied by the physiotherapist and the displacement of the targets on his hands were recorded. Parameters were also measured and calculated to compare against other studies. Time lags between force time histories and displacement time histories were observed on both children and adults. Different time lags resulted in different shapes of the force–displacement curves. Factors including respiration, muscle contraction and loading pattern are part of the assumptions used to explain this phenomenon. The maximum displacements of the paediatric and adult trunks were 18 and 44 mm, respectively, with a maximum load of 208 and 250 N, respectively. This study provides a better explanation of the peculiar force–displacement characteristics of both living and active children and adults under a non-injurious, low-rate compression condition. Complementary data (e.g. muscle activity and breathing) should be collected in the future to go towards in vivo human trunk modelling.